Unveiling the dynamics of acetylation and phosphorylation in SGBS and 3T3-L1 adipogenesis - Alix Sarah Aldehoff; Isabel Karkossa; Cornelius Goerdeler; Laura Krieg; Jana Schor; Beatrice Engelmann; Martin Wabitsch; Kathrin Landgraf; Jörg Hackermüller; Antje Körner; Ulrike Rolle-Kampczyk; Kristin Schubert; et al. (iScience, 2024)
Summary: Obesity, characterized by enlarged and dysfunctional adipose tissue, is among today’s most pressing global public health challenges with continuously increasing prevalence. Despite the importance of post-translational protein modifications (PTMs) in cellular signaling, knowledge of their impact on adipogenesis remains limited. Here, we studied the temporal dynamics of transcriptome, proteome, central carbon metabolites, and the acetyl- and phosphoproteome during adipogenesis using LC-MS/MS combined with PTM enrichment strategies on human (SGBS) and mouse (3T3-L1) adipocyte models. Both cell lines exhibited unique PTM profiles during adipogenesis, with acetylated proteins being enriched for central energy metabolism, while phosphorylated proteins related to insulin signaling and organization of cellular structures. As candidates with strong correlation to the adipogenesis timeline we identified CD44 and the acetylation sites FASN_K673 and IDH_K272. While results generally aligned between SGBS and 3T3-L1 cells, details appeared cell line specific. Our datasets on SGBS and 3T3-L1 adipogenesis dynamics are accessible for further mining.